Prostate Cancer: New serum tumor marker for monitoring patients - McCormack, M. (1992)
As the incidence of prostatic cancer rises, family physicians can expect to diagnose and treat increasing numbers of patients with this disease. Recent research has uncovered a new serum tumor marker (prostate-specific antigen), which is useful in patient monitoring and which eventually could be used in screening. A current review of available serum tumor markers is presented.